The Japanese Version of the Adolescent Time Inventory–Time Attitudes (ATI-TA) Scale: Internal Consistency, Structural Validity, and Convergent Validity. (March 2019) - Chishima, Yuta; Murakami, Tatsuya; Worrell, Frank C.; Mello, Zena R.
In this study, we translated the Adolescent Time Inventory–Time Attitudes (ATI-TA) scale into Japanese and examined the internal consistency and structural and convergent validity of ATI-TA scores in a sample of 383 Japanese high school students aged 15 to 18 years. The ATI-TA consists of six subscales assessing two valences (positive and negative) for each of three time periods (past, present, and future). Internal consistency estimates for scores on the ATI-TA were over .79. Confirmatory factor analysis indicated that a six-factor model yielded the best fit to scores. Correlations among ATI-TA scores, time attitudes assessed by the semantic differential method, educational career planning, and self-esteem were consistent with our hypotheses. Our results provide evidence that scores on the Japanese version of the ATI-TA are reliable and valid, and thus potentially useful for research in this cultural context.